2018
DOI: 10.1371/journal.pntd.0006823
|View full text |Cite
|
Sign up to set email alerts
|

VDR polymorphism, gene expression and vitamin D levels in leprosy patients from North Indian population

Abstract: BackgroundLeprosy is a chronic infectious disease caused by Mycobacterium leprae and mainly affects skin, peripheral nerves. Vitamin D receptor (VDR) gene polymorphism has been found to be associated with leprosy. Vitamin D has been shown to control several host immunomodulating properties through VDR gene. Vitamin D deficiency was also found to be linked to an increased risk for several infections and metabolic diseases.ObjectiveIn the present study, we investigated the association of VDR gene polymorphism, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…The findings are in concordance with one of the study in Chinese Han population showing association of ‘ff’ genotype with susceptibility to TB 9 . Similar findings were observed in a north Indian population showing significant association of Fok1 VDR polymorphism with leprosy 16 . However, in other studies from Egypt and India, no significant association was observed for VDR Fok1 polymorphism with susceptibility to TB 10,17 .…”
Section: Discussionsupporting
confidence: 88%
“…The findings are in concordance with one of the study in Chinese Han population showing association of ‘ff’ genotype with susceptibility to TB 9 . Similar findings were observed in a north Indian population showing significant association of Fok1 VDR polymorphism with leprosy 16 . However, in other studies from Egypt and India, no significant association was observed for VDR Fok1 polymorphism with susceptibility to TB 10,17 .…”
Section: Discussionsupporting
confidence: 88%
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“…Low levels of expression, VDR stability and vitamin D3-VDR interaction were related to leprosy and its complications (44). It has been shown that some individuals with normal levels of vitamin D3, but with low levels of VDR protein, had a high bacilloscopic index and type 2 reaction (45).…”
Section: Discussionmentioning
confidence: 99%